Analysis of Customer Resistance to Internet Network Tariffs at Plasa Telkom Gunungsitoli - Gea, Desman; Ndraha, Ayler Beniah; Harefa, Peringatan; Waruwu, Eliyunus (Dinasti Publisher, 2024)
This research aims to analyze customer resistance to the internet network tariff policy at Plasa Telkom Gunungsitoli, focusing on the inconsistency of tariffs applied by PT Telekomunikasi Indonesia. Using a descriptive qualitative approach, this study collected primary data through direct interviews and secondary data from documentation, and analyzed the data using the Miles and Huberman model. The results show customer dissatisfaction with tariff inconsistency and service quality that does not match the price paid, leading to customer resistance. The findings also highlight the importance of transparency, improved service quality, and responsiveness to complaints in maintaining customer trust and satisfaction. In addition, incentivizing loyal customers and effective information management are important strategies in overcoming customer resistance. In conclusion, to deal with customer resistance, PT Telekomunikasi Indonesia needs to adopt a holistic approach that includes tariff policy transparency, service quality improvement, and continuous policy evaluation. The implementation of this strategy will increase customer satisfaction and strengthen the company's reputation as a leading telecommunications service provider.